Elafibranor for the treatment of NAFLD: One pill, two molecular targets and multiple effects in a complex phenotype - Sookoian, Silvia Cristina (2016)
Article commented: Elafibranor, an Agonist of the Peroxisome Proliferator-Activated Receptor-α and -δ, Induces Resolution of Nonalcoholic Steatohepatitis Without Fibrosis Worsening.